Cover Image, Volume 530, Issue 2. Issue 2 (29th December 2021) - Wernitznig, Stefan; Rind, F. Claire; Zankel, Armin; Bock, Elisabeth; Gütl, Daniel; Hobusch, Ulrich; Nikolic, Manuela; Pargger, Lukas; Pritz, Elisabeth; Radulović, Snježana; Sele, Mariella; Summerauer, Susanne; et al.
Abstract : The cover image is based on the Research Article The complex synaptic pathways onto a looming‐detector neuron revealed using serial block‐face scanning electron microscopy by Stefan Wernitznig et al., https://doi.org/10.1002/cne.25227 .